Osteogenesis of Crouzon-Mutated Cells in an Experimental Model. Issue 1 (January 2018) - Alcon, Andre; Metzler, Philipp; Eswarakumar, Jacob; Wilson, Alexander T.; Steinbacher, Derek M.
Abstract : Abstract: Crouzon syndrome is an autosomal-dominant congenital disease due to a mutation in the fibroblast growth factor receptor 2 protein. The purpose of this study is to evaluate wound-healing potential of Crouzon osteoblasts and adipose-derived stem cells (ADSCs) in a murine model. Parietal skull defects were created in Crouzon and mature wild-type (WT) CD-1 mice. One group of WT and Crouzon mice were left untreated. Another group was transplanted with both WT and Crouzon adipose-derived stem cells. Additional groups compared the use of a fibrin glue scaffold and periosteum removal. Skulls were harvested from each group and evaluated histologically at 8-week and/or 16-week periods. Mean areas of defect were quantified and compared via ANOVA F-test. The average area of defect after 8 and 16 weeks in untreated Crouzon mice was 15.37 ± 1.08 cm 2 and 16.69 ± 1.51 cm 2, respectively. The average area of the defect in untreated WT mice after 8 and 16 weeks averaged 14.17 ± 1.88 cm 2 and 14.96 ± 2.26 cm 2, respectively. WT mice with autologous ADSCs yielded an average area of 15.35 ± 1.34 cm 2 after 16 weeks while Crouzon mice with WT ADSCs healed to an average size of 12.98 ± 1.89 cm 2 . Crouzon ADSCs transplanted into WT mice yielded an average area of 15.47 ± 1.29 cm 2 while autologous Crouzon ADSCs yielded an area of 14.22 ± 3.32 cm 2 . ANOVA F-test yielded P  = .415. The fibroblast growth factor receptor 2 mutation in Crouzon syndrome does not promote reossification of critical-sized defects in mature WT and Crouzon mice. Furthermore, Crouzon ADSCs do not possess osteogenic advantage over WT ADSCs.